Protein degradation in the rumen : the effect of basal diet and a comparison of techniques - Cronje, Pierre Bernard (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.Sc. (Agric.)) -- University of Stellenbosch, 1984.